THE IMPRINT OF BASALT ON THE GEOCHEMISTRY OF SILICIC MAGMAS - Snyder D.; Tait S. (My University, 1998)
We propose that the fluid mechanics of magma chamber replenishment leads to a novel process whereby silicic magmas can acquire an important part of their chemical signatures. When flows of basaltic magma enter silicic magma chambers, they assume a `fingered' morphology that creates a large surface area of contact between the two magmas. This large surface area provides an opportunity for significant chemical exchange between the magmas by diffusion that is enhanced by continuous flow of silicic liquid traversing the basalt through thin veins. A quantitative analysis shows that a basaltic magma may thereby impart its trace-element and isotopic characteristics to a silicic magma. Depending on concentration differences and diffusion coefficients for the given components, this new mechanism may be as important as crystal fractionation and assimilation in producing the compositional diversity of silicic magmas. It may explain concentration gradients in silicic ash-flow tuffs and should be considered when interpreting the isotopic signatures of silicic rocks, even in the overt absence of mixing. For example, we show that, for several well studied, compositionally graded ash-flow tuffs, the concentrations and isotopic ratios of important geochemical tracers such as strontium could be largely due to this flow-enhanced diffusion process.
Keywords: FLUID DYNAMICS; DIFFUSION; MAGMAS; BASALTIC COMPOSITION; ACIDIC COMPOSITION